The Police in the Basra Province 1869-1921 - Farhood, Dr Hamidah Maki (Thi Qar Arts Journal, 2023)
The Ottoman provinces were divided militarily since the early nineteenth century into seven regions, each with a complete regular army of infantry, cavalry and artillery. As for the police, this device was established under a regulation issued by the High Gate in 1845. However, this security device was unable to perform the tasks entrusted to it due to its weakness, the small number of its members, and the rampant corruption in its structure. Despite all the efforts made by the Ottoman governors to improve this device, it remained suffering from poor management and equipment until the collapse of the Ottoman state. After the occupation of Iraq by the British forces, attention was paid to the police, its formations, equipment, and increasing the number of its members, in order to carry out the tasks that fall on its responsibility as a security device to protect the security of the occupied cities and the roads of movement of those forces and their supplies. The Indian model was followed in the beginning of the formation of this device, where police officers were brought from India and Aden when Basra, Amara and Nasiriyah were occupied. Then the local police (Shabana) were recruited in the villages and remote areas and they were from the Arab population. The affairs of this force were gradually organized, as the correct foundations were laid for it, which became the edifice on which the police forces relied later. This force was initially managed by the British officers, headed by Colonel (Brixot), the Inspector General of Police.